2012
DOI: 10.1080/02786826.2012.665514
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Phase State and Water Content in Ozonolysis of Internal Mixtures of Maleic Acid and Ammonium Sulfate Particles

Abstract: The ozonolysis of maleic acid/ammonium sulfate (MA/AS, 30/70 wt%) internal mixtures was investigated at various relative humidities (RHs) (80%, 55%, 30%, and <5%) and physical states (aqueous and crystalline solid). Complementary laboratory techniques-an electrodynamic balance coupled with in situ Raman spectroscopy and a reaction flow cell coupled with offline ion chromatography (IC)-were employed to probe the mass changes, spectroscopic changes, product identities, and post-reaction hygroscopic changes in oz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Reactive transformations in levitated droplets have largely been investigated with nondestructive optical probes 15,[17][18][19][20][21][22][23] . While functional group information is available from Raman spectroscopy, it cannot always provide specific information on the composition of a droplet undergoing chemical transformations.…”
mentioning
confidence: 99%
“…Reactive transformations in levitated droplets have largely been investigated with nondestructive optical probes 15,[17][18][19][20][21][22][23] . While functional group information is available from Raman spectroscopy, it cannot always provide specific information on the composition of a droplet undergoing chemical transformations.…”
mentioning
confidence: 99%
“…Aqueous MA was found to be more reactive towards ozone than crystalline MA. Interestingly, they also found that higher water content favors more efficient ozonolysis, although the concentration of MA is accordingly lower (Chan and Chan, 2012). Furthermore, ozonolysis of optically trapped bioaerosol particles has also been reported.…”
Section: Multiphase Oxidation Of Aerosol Particlesmentioning
confidence: 95%
“…The oleic acid ozonolysis was completed in ∼ 3000 s, but the decrease in droplet volume still lasts for an additional ∼ 5000 s due to the slow volatilization of the products (Dennis-Smither et al, 2012). Chan and Chan (2012) studied the roles of the phase state and water content in the ozonolysis of maleic acid (MA) and AS mixed particles. Aqueous MA was found to be more reactive towards ozone than crystalline MA.…”
Section: Multiphase Oxidation Of Aerosol Particlesmentioning
confidence: 99%
“…Interestingly, they also found that higher water content favors more efficient ozonolysis, although the concentration of MA is accordingly lower. (Chan and Chan, 2012) Furthermore, ozonolysis of optically trapped bioaerosol particles has also been reported. In general, lipids and proteins show distinct v(C-H) peaks at 2855 cm -1 and 2928 cm -1 , respectively.…”
Section: Multiphase Oxidation Of Organic Aerosol Particlesmentioning
confidence: 98%